Prevention of Lysosomal Storage Diseases and Derivation of Mutant Stem Cell Lines by Preimplantation Genetic Diagnosis. (26th December 2012) - Altarescu, Gheona; Beeri, Rachel; Eiges, Rachel; Epsztejn-Litman, Silvina; Eldar-Geva, Talia; Elstein, Deborah; Zimran, Ari; Margalioth, Ehud J.; Levy-Lahad, Ephrat; Renbaum, Paul
Abstract : Preimplantation genetic diagnosis (PGD) allows birth of unaffected children for couples at risk for a genetic disorder. We present the strategy and outcome of PGD for four lysosomal storage disorders (LSD): Tay-Sachs disease (TSD), Gaucher disease (GD), Fabry disease (FD), and Hunter syndrome (HS), and subsequent development of stem cell lines. For each disease, we developed a family-specific fluorescent multiplex single-cell PCR protocol that included the familial mutation and informative markers surrounding the mutation. Embryo biopsy and PGD analysis were performed on either oocytes (polar bodies one and two) or on single blastomeres from a six-cell embryo. We treated twenty families carrying mutations in these lysosomal storage disorders, including 3 couples requiring simultaneous analysis for two disorders (TSD/GD, TSD/balanced Robertsonian translocation 45XYder(21;14), and HS/oculocutaneus albinism). These analyses led to an overall pregnancy rate/embryo transfer of 38% and the birth of 20 unaffected children from 17 families. We have found that PGD for lysosomal disorders is a safe and effective method to prevent birth of affected children. In addition, by using mutant embryos for the derivation of stem cell lines, we have successfully established GD and HS hESC lines for use as valuable models in LSD research.